Consumer Hypnotic-Like Suggestibility: Possible Mechanism in Compulsive Purchasing. Issue 1 (August 2013) - Prete, M. Irene; Guido, Gianluigi; Pichierri, Marco
The authors hypothesize a concept, Consumer Hypnotic-Like Suggestibility (CHLS), defined as an altered state of consciousness, as a state causing a tendency to respond positively to messages aimed at inducing consumers to make unplanned purchases. This study aims to investigate the associations of CHLS with interpersonal variables and compulsive purchasing—a frequent and uncontrollable preoccupation with buying or impulses to buy. A study was conducted on a sample of 232 subjects ( n = 111 men; M age = 41 yr.), through the administration of a questionnaire, which measured: CHLS, compulsive purchasing, consumer susceptibility to interpersonal influence (the necessity to enhance one's image in the opinion of others through the consumption of products), and consumer atmospherics, i.e., environmental stimuli known to influence purchasing decisions. Modeling and mediation analyses suggested that internal and external drivers—Consumer Susceptibility to Interpersonal Influence and atmospherics—are positively related to CHLS which affects compulsive purchasing.